Determining the Factors Influencing the Use of Assistive Technology in Teaching Mathematics to Visually Impaired Learners in Kenyan Special Primary Schools - Chege Mary Wairimu; Joel M. Chomba; Beatrice Bunyasi Awori (Selected Topics in Humanities and Social Sciences Vol. 4, 2021)
When compared to the other examinable courses, students with visual impairments (VI) in Kenyan primary schools do badly in Mathematics. In this regard, the purpose of this study was to determine the characteristics that influence the usage of Assistive Technology (AT) at teaching Mathematics to learners with VI in Kenya’s special primary schools for the blind.The study used a descriptive research approach to recruit 76 VI students of class seven and eight, as well as 10 Mathematics teachers from five special primary schools. The 10 teachers were chosen using purposeful sampling, while the 20 VI students were chosen using simple random sampling.Data was collected using interview instructions and an observation checklist. Inadequate time for syllabus coverage, expensive cost of AT devices, inadequate teacher training in the usage of AT devices, restrictive curriculum, and negative attitudes of learners were identified as important variables impacting AT device utilisation in the study.According to the study, the government should invest more funds for assistive technology equipment and undertake regular classroom supervision to ensure efficient use of AT devices.